2015
DOI: 10.1371/journal.pone.0132497
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin Mitigates Gastric Ulcer in Ischemia/ Reperfused Rats: Involvement of PPAR-γ, NF-κB and Nrf2/HO-1 Signaling Pathways

Abstract: Mangiferin (MF), a xanthonoid from Mangifera indica, has been proved to have antisecretory and antioxidant gastroprotective effects against different gastric ulcer models; however, its molecular mechanism has not been previously elucidated. Therefore, the aim of this study was to test its modulatory effect on several signaling pathways using the ischemia/reperfusion model for the first time. Animals were treated with MF, omeprazole (OMP), and the vehicle. The mechanistic studies revealed that MF mediated its g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 61 publications
5
47
1
Order By: Relevance
“…1) indicates that OM in concentrations up to 100 μM can be used to investigate its effects on HO-1 expression in HPMEC. Consistent with our study, OM has been reported to similarly increase gastric HO-1 expression in rats (Mahmoud-Awny et al , 2015) and humans (Becker et al , 2006). However, other studies suggest that OM fails to induce intestinal HO-1 expression (Higuchi et al , 2009; Yoda et al , 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1) indicates that OM in concentrations up to 100 μM can be used to investigate its effects on HO-1 expression in HPMEC. Consistent with our study, OM has been reported to similarly increase gastric HO-1 expression in rats (Mahmoud-Awny et al , 2015) and humans (Becker et al , 2006). However, other studies suggest that OM fails to induce intestinal HO-1 expression (Higuchi et al , 2009; Yoda et al , 2010).…”
Section: Discussionsupporting
confidence: 92%
“…It is also possible that OM may regulate HO-1 expression partly via these transcription factors and signaling pathways. Although previous studies have shown that OM and its S-enantiomer, esomeprazole, increases gastric (Becker et al , 2006; Mahmoud-Awny et al , 2015) and pulmonary (Ghebremariam et al , 2015) HO-1 expression, respectively, the mechanisms of HO-1 induction were not investigated. To the best of our knowledge, this is the first study to demonstrate that Nrf2 is directly involved in OM-mediated induction of HO-1 in HPMEC in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Although Mahmoud-Awny et.al. [43] observed that OM increases Nrf2 mRNA levels in rats with an ischemic/reperfusion insult, OM had no effect on the Nrf2 mRNA levels (Fig. 3A) in our study.…”
Section: Resultscontrasting
confidence: 44%
“…Studies have shown that, in gastric ulcers induced by IR after reperfusion process, ROS are generated from xanthine oxidase and the activation of neutrophils, leading to gastric mucosa lipid peroxidation (LPO), in combination with acid-gastric secretion process, results in extremely harmful ulcerogenic injury and cell death (Mahmoud-Awny et al, 2007). Thus, it is fundamental to assess lipid peroxidation (LPO) in gastric ulcers induced by IR experimental protocol.…”
Section: Resultsmentioning
confidence: 99%